The Networks of Global Journalism: Global news construction through the collaboration of global news startups with freelancers. (2nd January 2017) - Hellmueller, Lea; Cheema, Sadia Ehsan; Zhang, Xu
Abstract : This study explores how recent global news startups have connected freelancers with traditional news organizations. Through 10 interviews with founders and editors, the results reveal a networked marketplace of global journalism: the startups build on new technologies as well as on-the-ground evidence as their business model and de-localize the distribution of news within a digital marketplace. Supplemented by a content analysis of their edited stories ( N = 226), global journalism as an outcome of this marketplace is discussed.